1994
DOI: 10.1111/j.1432-1033.1994.tb18803.x
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulphate covalently cross‐links the three polypeptide chains of inter‐α‐trypsin inhibitor

Abstract: Inter-a-trypsin inhibitor (ITI) is a tight complex of three different proteins : bikunin and two heavy chains H1 and H2. In order to demonstrate that the three chains are covalently linked by a chondroitin sulphate chain as previously proposed [Enghild, J. J., Salvesen, G., Hefta, S. A., Thogersen, I. B., Rutherford, S. and Pizzo, S. V. (1991) J. Biol. Chem. 266, IT1 was extensively digested with thermolysin and the glycosaminoglycan-containing fragment was isolated from the digest by ion-exchange chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 18 publications
0
53
0
Order By: Relevance
“…2G). Biochemical analysis has shown that the C-terminal ends of the two heavy chains in I␣I are covalently linked to the chondroitin sulfate chain of bikunin (6). In the electron micrographs of I␣I, a small globule can be seen in the middle of the strand connecting the larger globular domains (Fig.…”
Section: Circular Dichroismmentioning
confidence: 99%
See 1 more Smart Citation
“…2G). Biochemical analysis has shown that the C-terminal ends of the two heavy chains in I␣I are covalently linked to the chondroitin sulfate chain of bikunin (6). In the electron micrographs of I␣I, a small globule can be seen in the middle of the strand connecting the larger globular domains (Fig.…”
Section: Circular Dichroismmentioning
confidence: 99%
“…It consists of bikunin, which has a molecular mass of about 25 kDa (1,2), and two other polypeptides of 75-80 kDa, the heavy chains 1 and 2 (H1 and H2) (3). Bikunin carries a 7-kDa chondroitin sulfate chain (4,5), which is linked to the ␣-carbons of the C-terminal amino acid residues of H1 and H2 through two ester bonds (6). Pulse-chase experiments with isolated hepatocytes have shown that the coupling of bikunin to the heavy chains occurs in the Golgi complex immediately after the chondroitin sulfate chain has been completed (7,8).…”
Section: Inter-␣-inhibitor (I␣i)mentioning
confidence: 99%
“…The members of the ITI family are a complex of heavy chain(s) and bikunin, both of which are connected by a chondroitin sulfate sugar chain. [6][7][8] The function of the ITI family is believed to be a protease inhibitor; however, the inhibitory activity of heavy chain-free bikunin is stronger than those of the ITI family. 17) A recently identified remarkable function of the ITI family is their extracellular matrix-stabilizing activity.…”
Section: Quantitation Of Ihrp In Human Plasmamentioning
confidence: 99%
“…[3][4][5] All of them have the unique structures, i.e., bikunin and heavy chain(s) are bridged by a chondroitin sulfate sugar chain. [5][6][7][8] The function of the ITI family is believed to be as a protease inhibitor, however, the extracellular matrix-stabilizing activity of the ITI family is noteworthy. 9,10) In spite of the sequence similarity, IHRP did not form a complex with bikunin because of the deletion of the consensus sequence (DPHFII) for the cleavage of the C-terminal fragment and the attachment to the chondroitin sulfate sugar chain of bikunin.…”
mentioning
confidence: 99%
“…In biosynthesis, the chondroitin 4-sulfate chain is synthesized on and attached to a serine residue of the L chain through the conventional carbohydrate-protein linkage structure GlcAp1-3Gal~1-3Gal~l-4Xyl~l-O-Ser (where GlcA represents D-gIUCUronic acid; Balduyck et al, 1986;Enghild et al, 1993). The H, chain is bound to the chondroitin 4-sulfate chain through a unique ester bond between the a-carboxylate of the COOH-terminal Asp and C6 OH of an internal GalNAc of the chondroitin 4-sulfate chain (Enghild et al, 1993), and the H, chain has also been demonstrated to be linked to the chondroitin 4-sulfate with similar architecture (Morelle et al, 1994). However, the formation mechanisms of such unique linkages between the chondroitin 4-sulfate and the heavy chains are unknown.…”
mentioning
confidence: 99%